Setting the second stage: the evolution of menopause & post-reproductive life - Sievert, Lynnette (Henry Stewart Talks, 2017)
Defining menopause, Cross-species comparisons in length of post-reproductive life, Menopause and post-reproductive life in hominin evolution, Hypotheses to explain evolution of menopause and post-reproductive life